STRESS-STRAIN STATE OF MULTILAYER POLYMER PIPES TAKING INTO ACCOUNT THE CREEP OF MATERIAL - Stepan Viktorovich Litvinov; Galina Mikhailovna Danilova-Volkovskaya; Anastasiya Evgen'evna Dudnik; Anton Sergeevich Chepurnenko (Современная наука и инновации)
The resolving equations for determining stress-strain state of multi-layer plastic pipes with internal pressure with the creep of the material. The problem is solved by the finite element method in two-dimensional case. There is a considerable redistribution of stresses between polymer layers and a reinforcing layer.